FORMATION OF TOILET SKILLS IN CHILDREN IN RUSSIA. PROBLEM ANALYSIS - G. A. Karkashadze; L. S. Namazova-Baranova; O. I. Maslova; U. N. Klochkova; S. N. Zorkin; E. V. Komarova (Union of pediatricians of Russia, 2012)
The article is devoted to one of the most pressing and largely discussed problems, not only in pediatrics, but also in pedagogy and psychology - toilet skills training for children. The authors formulate a number of tasks required to solve the problem of the correct toilet training the child, and discussion questions are the following: at what age to start correctly this skill forming, what is the conscious use of the potty? In addition, the problem of toilet training skills was shown in terms of different specialists: doctors, as well as parents, manufacturers, and law. There was shown an important role in solving this problem at the state level of professional organizations, as well as the need for uniform terminology with the same understanding of their meaning by all stakeholders.